2015
DOI: 10.1007/s12520-015-0229-4
|View full text |Cite|
|
Sign up to set email alerts
|

Colour in context. Pigments and other coloured residues from the Early-Middle Holocene site of Takarkori (SW Libya)

Abstract: We present the multidisciplinary investigation of pigments and artefacts with traces of colour from the Early- Middle Holocene site of Takarkori, located in the Tadrart Acacus Mountains (central Sahara, SW Libya). Here, geological, archaeological, taphonomic and chemical studies (Raman, Fourier-transform infrared, X-ray powder diffraction, gas chromatography–mass spectrometry) are used to examine a vast range of artefacts (raw materials, grinding stones,\ud painted items, as well as lithic, bone, wooden and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…Dutrisac et al [77] claims that jarosite group minerals were being exploited at Rio Tinto in Spain from 1200 BCE. Jarosite yellow ochres have been identified on painted objects from the 9 ka site of Takarkori, Libya by di Lernia et al [82] and jarosite has also been detected in Australian Aboriginal rock art in the Kimberley region [83,84].…”
Section: Wads: Manganese Ochresmentioning
confidence: 94%
“…Dutrisac et al [77] claims that jarosite group minerals were being exploited at Rio Tinto in Spain from 1200 BCE. Jarosite yellow ochres have been identified on painted objects from the 9 ka site of Takarkori, Libya by di Lernia et al [82] and jarosite has also been detected in Australian Aboriginal rock art in the Kimberley region [83,84].…”
Section: Wads: Manganese Ochresmentioning
confidence: 94%
“…A comprehensive discussion on the origin of hematite (natural or by heating goethite) and on iron oxide phases is given; carbon black, anatase, Mn 3 O 4 are observed in some samples. Di Lernia et al analysed pigments and coloured residues from the Early–Middle Holocene site of Takarkori (SW Libya), and found jarosite and kaolinite, in addition to hematite and goethite. A recent work by Huntley et al on ‘mulberry rock art’ reports at least two distinct mineral mulberry pigments, jarosite KFe 3 (OH) 6 (SO 4 ) 2 and hematite, on the basis of elemental analysis (SEM‐EDS analysis and X‐ray fluorescence spectroscopy).…”
Section: Introductionmentioning
confidence: 99%
“…Casein binder has a long history. It has been found acting as a binder in the painted stones of the 8000-year-old Takarkori Ruins in the Libyan Sahara (Di Lernia et al, 2016), and has also been found in Ancient Egyptian relics (Ren et al, 2016). It is also commonly used in traditional European murals, and continues to be used until now.…”
Section: Discussionmentioning
confidence: 99%